Cooking methods employing natural anti-oxidant food additives effectively reduced concentration of nephrotoxic and carcinogenic aristolochic acids in contaminated food grains. (30th October 2018) - Li, Weiwei; Chan, Chi-Kong; Wong, Yee-Lam; Chan, K.K. Jason; Chan, Ho Wai; Chan, Wan
Highlights: Aristolochic acids (AAs) from Aristolochia weed contaminated food grains of Balkans. Chronic food poisoning by AA via AA-tainted food resulted in renal fibrosis. Cooking employing anti-oxidants lowered level/toxicity of AA in AA-tainted food. Boiling with aminothiols/GSH converted mutagenic AA to non-mutagenic aristolic acids. Cooking with Mg/ascorbic acid chemically reduced AA to non-mutagenic aristolactams. Abstract: Emerging evidence suggests that aristolochic acids (AA) produced naturally by a common weed Aristolochia clematitis in the cultivation fields is contaminating the food products in Balkan Peninsula and acting as the etiological agent in the development of Balkan endemic nephropathy. In this study, we investigated the combined use of natural anti-oxidative "food additives" and different cooking methods to find a solution for the widespread contamination of AA in food products. The results indicated that the addition of healthy dietary supplements (such as cysteine, glutathione, ascorbic acid, citric acid and magnesium) during cooking, is a highly efficient method in lowering the concentration of AA in the final food products. Because previous observation indicated one of the toxicological mechanisms by which AA exert its toxicity is to induce oxidative stress in internal organs, it is anticipated that these added anti-oxidants will also help to attenuate the nephrotoxicity of AA.